(3JMaI GdENhGf hehGgH GdEeJfGf aj efGbH GdTjN QVhGfs - (3CMeO Hf ehSi Hf YHO Gddg Hf eMeO GdMQGaj GdCfOdSj,J (B1034 (3g` s
(3ChdgG (B:s
(3bGd(B:(3KdGKI , hge GdChdjGA hSHYhf hge GdTaYGA , hCQHYhf hge GdChJGO s
(3BNQgG (B:s
(3hgh eG hLOJg HNWg(B: (3cfJ PGJ jhe eY SjOj YHOGdQMef QMeg Gddg, hcGf eYg cJGH GdebJQM , abGe dMGLI Ke bGd (B: (3NWGHg jMb dh de jcf YfOc s
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B239 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B93 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs